Sie sind auf Seite 1von 2

• 0 • f x ( 0 ) ,
• 0 • f x ( 0 ) ,

0

f

x (0) ,

, x (T 1) R n

x (i) 2 R 0 i < T

ρ > 0 f w R n w 2 = 1 i

0 < ρ f(x (i) ) · w, x (i) .

T R 2

ρ

2

k

k n O(k · log n) Ω(k · log n) 0 < µ 1 k n 1µ

n,k k n

( n,k ) = Ω(k · log n) .

k = 1

k = o(n) X = {0, 1} n × {1}

f(x 1 ,

, x n ) = x 1 ∨ ··· ∨ x k

k = 1

f k : {0, 1} n → {−1, +1}

n

f k (x 1 ,

,

x n ) = 1

⇐⇒

i=1

x i k

f k

m k m < n

f : {0, 1} n → {−1, 1}

O(n 2 ·W 2 )

f f (x) = ( w, x t)

w 1 ,

, w n Z t Z |w 1 |,

,

|w n | |t| ≤ W

x (i) = ((1) i ,

,

(1) i , (1) i+1 , 0,

i

, 0) R n

f (x (i) ) = (1) i+1 1 i n Ω(2 n )

n : {0, 1} n × {0, 1} n → {−1, 1}

n (x, y) =

+1

1

n

i=1 x i 2 i1 n

i=1 y i 2 i1 ,

n ( w, x u, y ) (w, u) n